Principal Leadership Innovation in Conflict Management - Beni Miftahul Huda; Muhammad Faisal Agha Farsen; Tamrin Fathoni; R.T. Monteiro (CV Edujavare Publishing, 2024)
The author wrote this paper with the aim of fulfilling a college assignment as well as education for school principals, where the principal is a central figure in managing all aspects related to education in a school institution, especially in this paper is how the figure of the principal must be alert in innovating to overcome all problems that arise during the education process. With all the limitations of time and material, this paper uses a qualitative research method because it is more effective by collecting journal texts that have been done by previous researchers. In short, innovation is change. Management according to the term or language comes from Latin, namely manus which has the meaning in English